(untitled) (CIPEEX, 2024)
THIS PAPER PRESENTS A MOBILE APPLICATION DESIGNED TO ELECTRONICALLY RECORD THE PATH OF CORA CORALINA, A 300 KM TRAIL CROSSING HISTORIC CITIES IN GOIS, BRAZIL. THE CURRENT MANUAL TRAIL COMPLETION PROCESS INVOLVES PILGRIMS GETTING THEIR PASSPORTS STAMPED AT EACH SECTION. THE PROPOSED APPLICATION STREAMLINES THIS PROCEDURE, ENABLING AUTOMATED PROGRESS RECORDING THROUGH SECTION-BASED PINGS. PILGRIMS CAN GENERATE A DIGITAL CERTIFICATE UPON FINISHING THE TRAIL. DEVELOPED USING REACT NATIVE, A CROSS-PLATFORM MOBILE DEVELOPMENT FRAMEWORK, THE APPLICATION UTILIZES NATIVE LIBRARIES TO FURNISH PILGRIMS WITH DIRECTIONS AND SECTION-SPECIFIC INFORMATION. PROGRESS DATA IS STORED IN THE PILGRIMS’ DEVICES, ALLOWING PINGS EVEN WHEN OFFLINE. THIS APPLICATION ENHANCES EFFICIENCY AND CONVENIENCE IN DOCUMENTING CORA CORALINA PATH COMPLETIONS WHILE PRESERVING THE REGION’S HISTORY AND CULTURE BY PROVIDING INSIGHTFUL INFORMATION ABOUT THE VISITED LOCATIONS.